2014
DOI: 10.1007/s00508-014-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endothelial cell density and corneal thickness in corneal grafts an average of 5 years after penetrating keratoplasty

Abstract: SummaryBackground Corneal transparency is a useful indicator for corneal function. Our aim was to investigate central corneal endothelial cells and corneal thickness in transplanted corneas at an average of 5.4 years after penetrating keratoplastyPatients and methods The study involved 68 perforated keratoplasty patients with at least a 1 year followup. Post-operatively, the central corneal endothelial layer was observed using a contact specular microscope. Central endothelial cell density, corneal thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Although the mean ECC in PKP group was reduced more than that in DALK group, but we found there was no statistically significant difference between the mean CCT of the two groups. The similar results were reported by Kettesy B [ 55 ], who found that there was no correlation between ECC and corneal thickness. Kus MM [ 56 ] proved that even if ECC decreased significantly, as long as an acceptable density was kept, the remaining cells compensated the loss well and corneal thickness remains normal.…”
Section: Discussionsupporting
confidence: 90%
“…Although the mean ECC in PKP group was reduced more than that in DALK group, but we found there was no statistically significant difference between the mean CCT of the two groups. The similar results were reported by Kettesy B [ 55 ], who found that there was no correlation between ECC and corneal thickness. Kus MM [ 56 ] proved that even if ECC decreased significantly, as long as an acceptable density was kept, the remaining cells compensated the loss well and corneal thickness remains normal.…”
Section: Discussionsupporting
confidence: 90%
“…Owing to the two properties of corneal endothelial cells, their function as a sodium pump to maintain transparency, and their lack of regeneration ability, the long-term optical clarity of the cornea after PKP is decided by the number, morphology, and function of donor endothelial cells [23]. However, in the presence of an irreversible ECD decline and dysfunction of the graft endothelium, endothelial decompensation of the PKP graft will occur.…”
Section: Changes In Corneal Endothelium After Penetrating Keratoplmentioning
confidence: 99%
“…According to previous studies, the density of endothelial cells after the first ten years following PKP has been reported to be 960 ± 470 [24], 840 ± 150 [25], or 642 ± 166 cells/mm 2 [26], and after the next ten years, the density was 855 [27] or 666 ± 284 cells/mm 2 [26] (Table 2 [3, 8, 9, 15, 23, 24, 2631]). The speed of endothelial cell loss was highest in the first year after PKP, with a rate of approximately 40% [30].…”
Section: Changes In Corneal Endothelium After Penetrating Keratoplmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results of alizarin red staining displayed that the ECD of the TE-HCE-transplanted rabbit corneas was 2703 ± 70.37 cells/mm 2 on average 358 days after PKP surgery, while that of control corneas was only 2509.90 ± 51.11 cells/mm 2 . The ECD of the TE-HCE-transplanted rabbit cornea was higher than that of the corneas in TE-HCE-transplanted rabbits and cats in our previous study (Fan TJ et al, 2011;Fan et al, 2013), and much higher than that of the corneas 12 months after endothelial keratoplasty in donated cornea-transplanted patients (<2000 cells/ mm 2 ) (Van Dooren et al, 2004;Kettesy et al, 2014;Lam et al, 2015;Yoeruek et al, 2015). Moreover, our results of H&E staining and SEM and TEM studies revealed that a continuous monolayer of corneal endothelial cells in hexagonal or polygonal morphology attached tightly to the de novo generated DM was reconstructed.…”
Section: Discussionmentioning
confidence: 99%